PENGARUH BIAYA PROMOSI TERHADAP PENINGKATAN JUMLAH MURID DI SEMPOA SIP SUMUT DAN ACEH - IVONE .; TRIANY WONGNUR; ARWIN .; LISA .; ELSERRA SIEMIN CIAMAS (JURNAL ILMIAH SIMANTEK, 2019)
Formal education is a structured and tiered education pathway which consists of basic education, secondary education, andhigher education. Non-formal education is an education pathway out of formal education that can be implemented in astructured and tiered way. While, informal education is the path of family and environmental education (Law No. 20 of 2003).The formulation of the problem in this study is "Is there any influence on the promotional cost towards the increasing numberof students at Sempoa SIP North Sumatra and Aceh?". The purpose of this study was to determine the effect of promotionalcosts towards the increasing number of students at Sempoa SIP North Sumatra and Aceh. The method used in this study isa quantitative associative method that aims to measure the effect of independent variables on the dependent variable. Datacollection is done through documentation studies. From the results of this study note that the independent variable (thepromotional costs) and the dependent variable (the increasing number of students) have a very strong relationship. This canbe seen from the calculation of the correlation coefficient which has a value of r = 0.894. The conclusion of this study isbased on the hypothesis test obtained comparisons of t arithmetic> t table (4.472> 3.364). Thus, the promotional costsincurred by companies with the increasing number of students have a strong and positive relationship.